Decrease in winter respiration explains 25% of the annual northern forest carbon sink enhancement over the last 30 years. Issue 5 (22nd March 2016) - Yu, Zhen; Wang, Jingxin; Liu, Shirong; Piao, Shilong; Ciais, Philippe; Running, Steven W.; Poulter, Benjamin; Rentch, James S.; Sun, Pengsen
Abstract: Aim Winter snow has been suggested to regulate terrestrial carbon (C) cycling by modifying microclimate, but the impacts of change in snow cover on the annual C budget at a large scale are poorly understood. Our aim is to quantify the C balance under changing snow depth. Location Non‐permafrost region of the northern forest area. Methods Here, we used site‐based eddy covariance flux data to investigate the relationship between depth of snow cover and ecosystem respiration ( R eco ) during winter. We then used the Biome‐BGC model to estimate the effect of reductions in winter snow cover on the C balance of northern forests in the non‐permafrost region. Results According to site observations, winter net ecosystem C exchange (NEE) ranged from 0.028 to 1.53 gC·m −2 ·day −1, accounting for 44 ± 123% of the annual C budget. Model simulation showed that over the past 30 years, snow‐driven change in winter C fluxes reduced non‐growing season CO2 emissions, enhancing the annual C sink of northern forests. Over the entire study area, simulated winter R eco significantly decreased by 0.33 gC·m −2 ·day −1 ·year −1 in response to decreasing depth of snow cover, which accounts for approximately 25% of the simulated annual C sink trend from 1982 to 2009. Main conclusion Soil temperature is primarily controlled by snow cover rather than by air temperature as snow serves as an insulator to prevent chilling impacts. A shallow snow cover has less insulation potential, causing colder soil temperatures and potentially lower respiration rates. Both eddy covariance analysis and model‐simulated results show that both R eco and NEE are significantly and positively correlated with variation in soil temperature controlled by variation in snow depth. Overall, our results highlight that a decrease in winter snow cover restrains global warming as less C is emitted to the atmosphere.